Antimicrobial stewardship in primary health care programs in humanitarian settings: the time to act is now - Claudia Truppa; Beatriz Alonso; Kate Clezy; Carole Deglise; Carole Dromer; Silvia Garelli; Carolina Jimenez; Rupa Kanapathipillai; Mohamad Khalife; Ernestina Repetto (Antimicrobial Resistance and Infection Control, 2023)
Abstract Fragile and conflict-affected settings bear a disproportionate burden of antimicrobial resistance, due to the compounding effects of weak health policies, disrupted medical supply chains, and lack of knowledge and awareness about antibiotic stewardship both among health care providers and health service users. Until now, humanitarian organizations intervening in these contexts have confronted the threat of complex multidrug resistant infections mainly in their surgical projects at the secondary and tertiary levels of care, but there has been limited focus on ensuring the implementation of adequate antimicrobial stewardship in primary health care, which is known to be setting where the highest proportion of antibiotics are prescribed. In this paper, we present the experience of two humanitarian organizations, Médecins sans Frontières and the International Committee of the Red Cross, in responding to antimicrobial resistance in their medical interventions, and we draw from their experience to formulate practical recommendations to include antimicrobial stewardship among the standards of primary health care service delivery in conflict settings. We believe that expanding the focus of humanitarian interventions in unstable and fragile contexts to include antimicrobial stewardship in primary care will strengthen the global response to antimicrobial resistance and will decrease its burden where it is posing the highest toll in terms of mortality.